The Effects of Nickel and Copper on Tropical Marine and Freshwater Microalgae Using Single and Multispecies Tests. (10th March 2023) - McKnight, Kitty S.; Gissi, Francesca; Adams, Merrin S.; Stone, Sarah; Jolley, Dianne; Stauber, Jenny
Abstract: Microalgae are key components of aquatic food chains and are known to be sensitive to a range of contaminants. Much of the available data on metal toxicity to microalgae have been derived from temperate single‐species tests with temperate data used to supplement tropical toxicity data sets to derive guideline values. In the present study, we used single‐species and multispecies tests to investigate the toxicity of nickel and copper to tropical freshwater and marine microalgae, including the free‐swimming stage of Symbiodinium sp., a worldwide coral endosymbiont. Based on the 10% effect concentration (EC10) for growth rate, copper was two to four times more toxic than nickel to all species tested. The temperate strain of Ceratoneis closterium was eight to 10 times more sensitive to nickel than the two tropical strains. Freshwater Monoraphidium arcuatum was less sensitive to copper and nickel in the multispecies tests compared with the single‐species tests (EC10 values increasing from 0.45 to 1.4 µg Cu/L and from 62 to 330 µg Ni/L). The Symbiodinium sp. was sensitive to copper (EC10 of 3.1 µg Cu/L) and less sensitive to nickel (EC50 >1600 µg Ni/L). This is an important contribution of data on the chronic toxicity of nickel to Symbiodinium sp. A key result from the present study was that three microalgal species had EC10 values below the current copper water quality guideline value for 95% species protection in slightly to moderately disturbed systems in Australia and New Zealand, indicating that they may not be adequately protected by the current copper guideline value. By contrast, toxicity of nickel to microalgae is unlikely to occur at exposure concentrations typically found in fresh and marine waters. Environ Toxicol Chem 2023;42:901–913. © 2023 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC.